Comparative evaluation of long pulse alexandrite laser and intense pulsed light systems for pseudofolliculitis barbae treatment with one year of follow up - Leheta Tahra (Wolters Kluwer Medknow Publications, 2009)
Background: Existing remedies for controlling pseudofolliculitis barbae (PFB) are sometimes helpful; however the positive effects are often short lived. The only definitive cure for PFB is permanent removal of the hair follicle. Aims: Our aim was to compare the efficacy of the Alexandrite laser with the intense pulsed light system in the treatment of PFB and to follow up the recurrence. Methods: Twenty male patients seeking laser hair removal for the treatment of PFB were enrolled in this study. One half of the face was treated with the long-pulse Alexandrite laser and the other half was treated with the IPL system randomly. The treatment outcome and any complications were observed and followed up for one year. Results: All patients exhibited a statistically significant decrease in the numbers of papules. Our results showed that the Alexandrite-treated side needed seven sessions to reach about 80% improvement, while the IPL-treated side needed 10-12 sessions to reach about 50% improvement. During the one year follow up period, the Alexandrite-treated side showed recurrence in very minimal areas, while the IPL-treated side showed recurrence in bigger areas. Conclusions: Our results showed that both systems might improve PFB but Alexandrite laser was more effective at reducing PFB than IPL.